2010
DOI: 10.1186/1471-2164-11-331
|View full text |Cite
|
Sign up to set email alerts
|

Functional and gene network analyses of transcriptional signatures characterizing pre-weaned bovine mammary parenchyma or fat pad uncovered novel inter-tissue signaling networks during development

Abstract: BackgroundThe neonatal bovine mammary fat pad (MFP) surrounding the mammary parenchyma (PAR) is thought to exert proliferative effects on the PAR through secretion of local modulators of growth induced by systemic hormones. We used bioinformatics to characterize transcriptomics differences between PAR and MFP from ~65 d old Holstein heifers. Data were mined to uncover potential crosstalk through the analyses of signaling molecules preferentially expressed in one tissue relative to the other.ResultsOver 9,000 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Briefly, the dataset containing gene identifiers and corresponding fold changes was uploaded into the web-delivered application, and each gene identifier was mapped to its corresponding gene object. The threshold for a significant association was determined by the p -value <0.01, becoming significant any score above 3 [24]; [25]. For all analyses, Fisher’s exact test was used to calculate a p -value and to determine a score for all networks that were ranked on the probability that a collection of genes equal to or greater than the number in a network could be achieved by chance alone.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the dataset containing gene identifiers and corresponding fold changes was uploaded into the web-delivered application, and each gene identifier was mapped to its corresponding gene object. The threshold for a significant association was determined by the p -value <0.01, becoming significant any score above 3 [24]; [25]. For all analyses, Fisher’s exact test was used to calculate a p -value and to determine a score for all networks that were ranked on the probability that a collection of genes equal to or greater than the number in a network could be achieved by chance alone.…”
Section: Methodsmentioning
confidence: 99%
“…The plethora of phenomena happening in this tissue during all the developmental phases make it suitable for study by 'omics' technologies; particularly useful has been application of microarray technology to study gene and miRNA expression. Several studies have been published about the use of microarray technologies to investigate transcriptomics adaptation of mammary gland during development, lactation, and involution (some references among others [34,[172][173][174][175][176]). Also the use of microarrays to study the miRNA in mammary gland development has seeing an increase in popularity [177][178][179].…”
Section: Unbiased Transcriptome: Novel Findings On Mammary Protein Symentioning
confidence: 99%
“…Interactions between parenchyma and mammary fat pad are also demonstrated in prepubertal ewes (Hovey et al 1998), suggesting the presence of epithelial paracrine factors that would exert a positive feedback on the surrounding stroma. Interestingly, in a paper of Piantoni et al (2010) the transcriptomic differences analysis on 65-day-old Holstein heifers showed a bidirectional regulation between mammary fat pad and parenchyma. Cytokines and growth factors preferentially released by parenchyma were related to cell cycle progression, while those released by fat pad were involved in lipid metabolism and molecular transport.…”
mentioning
confidence: 99%
“…Cytokines and growth factors preferentially released by parenchyma were related to cell cycle progression, while those released by fat pad were involved in lipid metabolism and molecular transport. Moreover, the expression and secretion of leptin in mammary fat pad were thought to influence the expression of BDNF in the parenchyma (Piantoni et al 2010). Other transcriptome analyses were separately conducted on epithelial and intralobular stromal compartments of non-lactating dairy cows 3 weeks prepartum.…”
mentioning
confidence: 99%